Scalar representations in the semantics of Japanese. From measurements to pragmatics –The case of dokoroka– - Grzelak, Szymon (Investigationes Linguisticae, 2019)
This study looks into the scalar properties exhibited by some grammaticalized (and subsequently pragmaticalized) expressions of Japanese that are lexically based on the noun tokoro ‘place’. In particular, the argument will be focused on a conjunctive particle p dokoroka q ‘q, let alone p’. In most cases, both p and q can be ascribed some pragmatically inferred scalar values reflecting gradable properties, but the assessment of such a common scale is difficult in some cases. We argue that such “non-scalar” instances of dokoro-ka, occurring in enumerations, can be represented as cardinalities in the semantic model.